Manajemen stress selama pandemi covid 19 pada wirausaha - Khasanah, Utari Nur; Khasanah, Putri Uswatun; Adhania, Isna Rahma; Astikawati, Hemalia; Husna, Aftina Nurul (Prosiding University Research Colloquium, 2022)
The purpose of this study was to explore information through case studies related to the management of women's work stress during the Covid-19 pandemic. This research method uses a qualitative method with a single instrumental case study approach. Data collection techniques used in this study were interviews, observation and documentation with 3 female entrepreneurs as sources. It can be concluded that the Covid-19 pandemic has had many impacts on all groups, especially a woman who has multiple roles in her life